Evolution of strategic issues: a 20-year analysis of public library planning in South Korea - Lee, Hye-Eun; Jeon, Kyungsun; Lee, Jisu (Malaysian Journal of Library and Information Science, 2023)
This study delves into the strategic issues faced by public libraries in South Korea spanning the period from 2003 to 2022. An extensive examination of 176 strategic planning documents from 17 local governments resulted in the selection and analysis of 75 documents using a strategic planning analysis model. The findings reveal that issues such as staff/training, collaboration/networks, information literacy, digital libraries, physical space, and collection emerged as major concerns in the strategic planning of public libraries in Korea. An analysis of the top issues’ distribution over five-year intervals showed that staff/training issues consistently held a high rank over the 20-year period, underscoring their enduring strategic importance. Conversely, collection-related issues started with a low rank between 2003 and 2007 but consistently rose in significance from 2008 to 2022, becoming crucial strategic considerations for public libraries. Notably, these trends align closely with the direction set by the Comprehensive Library Advancement Plan at the national level for each period. The study underscores how the national-level development plan for libraries significantly influences the detailed strategic planning directions of local public libraries.